KHALID’S MANEUVER; A NEW APPROACH TO GROCCO’S SIGN IN PATIENTS WITH PLEURAL EFFUSION - Muhammad Khalid Azam (Army Medical College Rawalpindi, 2020)
Objective: To compare the usefulness of Grocco’s sign with an alternative method, Khalid’s maneuver, which does not require any change in patient’s position to elicit Grocco’s sign.